Community perceptions and personal accounts of HIV discordance in rural western Kenya. Issue 3 (28th September 2018) - Ondenge, Ken; Odero, Isdorah; Awuonda, Eucabeth; Omoro, Tereza; Kibogo, Michael; Otieno, George; Ongwena, Pauline; Gust, Deborah A
Abstract : Among HIV-discordant couples, the literature is sparse regarding issues related to stigma, relationships and coping. Objectives were to explore: 1) perceptions about discordant HIV status; 2) understanding of HIV discordancy; 3) effects of discordancy on couples; and 4) adaptation and coping strategies for discordant HIV status. A survey was administered to 202 members of heterosexual discordant couples in rural western Kenya. In addition, to understand the community perspective, in-depth interviews (IDI) ( n = 26) and focus group discussions (FGD) ( n = 10) were conducted with community opinion leaders, healthcare workers and members of discordant couples. More than 70% of men (73.4%) and women (80.4%) surveyed agreed that their relationship changed for the worse when they disclosed their HIV status to their partner. Participants of IDIs and FGDs provided several explanations for discordancy including the perception that discordancy is a lie, the negative partner has "thick blood", HIV infection is a punishment for sexual promiscuity or cultural disobedience, and that HIV is a punishment from God. Members of discordant couples reported experiencing tension and fear, stigma and rejection, and changes in partner support. Adaptation and coping strategies included counselling, sero-sorting and pursuing concordancy with the uninfected partner. HIV discordancy in a relationship can potentially cause long-term negative emotional and physical consequences. There is an acute need to develop and disseminate locally sensitive HIV-discordant couple counselling messages, and to provide couple-centred HIV care and treatment. Communication can help couples rebuild and rebalance their relationship and adjust to a new normal.